Deposition of Ag/a‐C:H nanocomposite films with Ag surface enrichment. Issue 11 (21st June 2017) - Vaidulych, Mykhailo; Hanuš, Jan; Steinhartová, Tereza; Kylián, Ondřej; Choukourov, Andrei; Beranová, Jana; Khalakhan, Ivan; Biederman, Hynek
Abstract : The nanocomposite films Ag/a‐C:H were prepared by vacuum‐based method which combines deposition of Ag nanoparticles by means of gas aggregation source (GAS) and PECVD deposition of a‐C:H matrix. The matrix was deposited in a mixture of Ar and n‐hexane on the substrates placed on the powered RF electrode facing the beam of Ag NPs from the GAS. Anisotropic plasma etching was used to increase Ag concentration on the surface of the coating. The influence of three types of plasma on the chemical composition of the coatings and on the size of Ag nanoparticles is described. It is shown that the best etching selectivity and thus the highest Ag surface concentration was reached in case of etching of grounded samples in low pressure oxygen plasma. This treatment enhances the short term antibacterial efficiency of produced coatings. Abstract : Hard Ag/a‐C:H nanocomposite coatings are deposit by combination of Gas aggregation source of nanoparticles with PECVD process. Etching of nanocomposites by different type of plasmas are studying in order to increase Ag surface concentration. It shows that oxygen etching increases Ag surface concentration up to 12 at .% which leads to the enhancement of antibacterial efficacy.